2010
DOI: 10.1002/jcp.22264
|View full text |Cite
|
Sign up to set email alerts
|

TNFalpha up‐regulates SLUG via the NF‐kappaB/HIF1alpha axis, which imparts breast cancer cells with a stem cell‐like phenotype

Abstract: Extracellular and intracellular mediators of inflammation, such as Tumor Necrosis Factor alpha (TNFα) and NF-kappaB (NF-κB), play major roles in breast cancer pathogenesis, progression and relapse. SLUG, a mediator of the epithelial-mesenchymal transition process, is over-expressed in CD44 + /CD24 − tumor initiating breast cancer cells and in basal-like carcinoma, a subtype of aggressive breast cancer endowed with a stem cell-like gene expression profile. Cancer stem cells also over-express members of the pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
152
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 173 publications
(166 citation statements)
references
References 63 publications
13
152
1
Order By: Relevance
“…Then, we tested the impact of the three NRs agonists on MS formation capability, which is currently considered the gold standard assay to assess the breast CSC phenotype in vitro. [6][7][8][9][10][11]33 We found that all the three NRs agonists reduce the number of MCF7-MS, but not of MCF10-MS with respect to control, and that IIF is the most active molecule (Figure 1c and Supplementary Figure 2a). Moreover, we compared the activity of NRs agonists on MS from tumor mammary gland (T-MS) and normal tissue samples (N-MS) ( Table 1 We finally proved that both in normoxia and hypoxia, NRs agonists induce cytotoxic effects in MS (Supplementary Figure 3a) and upregulate their cognate receptors (Supplementary Figure 3b).…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…Then, we tested the impact of the three NRs agonists on MS formation capability, which is currently considered the gold standard assay to assess the breast CSC phenotype in vitro. [6][7][8][9][10][11]33 We found that all the three NRs agonists reduce the number of MCF7-MS, but not of MCF10-MS with respect to control, and that IIF is the most active molecule (Figure 1c and Supplementary Figure 2a). Moreover, we compared the activity of NRs agonists on MS from tumor mammary gland (T-MS) and normal tissue samples (N-MS) ( Table 1 We finally proved that both in normoxia and hypoxia, NRs agonists induce cytotoxic effects in MS (Supplementary Figure 3a) and upregulate their cognate receptors (Supplementary Figure 3b).…”
Section: Resultsmentioning
confidence: 79%
“…This phenomenon is paralleled by the hampering of pro-inflammatory NF-kB/IL6 axis and associates with the downregulation of MS regulatory genes (SLUG, Notch3, Jagged1). 6,7,9,10 We also report that, at variance with the other NRs agonists, the PPARa specific agonist WY exerts a promoting role on MS formation and on the accompanying pro-inflammatory phenotype.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations